Prioritization of the barriers to integrated modular buildings (IMBs) in developing countries: Nigerian construction professionals’ perspectives - Akinsanmi Akindeinde; Joseph Akinola; Lekan Ojo; Augustine Okechukwu (Journal of Construction Project Management and Innovation)
Integrated modular building (IMBs) enhance construction performance, quality, and productivity. However, in developing economies, adoption is impeded by challenges that hinder efficiency and sustainability. The study investigated and prioritized the barriers associated with IMBs through purposive sampling of experienced construction professionals in IMBs. Of the various statistical analyses, the fuzzy synthetic evaluation (FSE) indicated that perception-related barriers are the most significant barrier to IMBs, among other barriers, namely skill-related, cost-related, technical-related, and regulation-related. The study holds significant implications for construction stakeholders to intensify efforts in addressing the identified barriers and raising awareness to facilitate more IMBs adoption. The study underscores the importance of tailored strategies aligned with these priorities to effectively address these barriers. Furthermore, enhancing awareness and implementing targeted interventions are crucial steps towards promoting IMBs and advancing sustainability in the construction sector.  Additionally, the prioritization of the barriers gives a logical order of required actions for construction stakeholders.